2022
DOI: 10.3389/fpubh.2022.997637
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and vaccination acceptance toward the human monkeypox among men who have sex with men in China

Abstract: BackgroundMSM individuals are at high risk of monkeypox infection, and judicious use of vaccines can control the outbreak. Therefore, we conducted a national cross-sectional survey to assess the vaccination willingness, associated factors, and related knowledges of monkeypox among MSM individuals in China.MethodsThis anonymous cross-sectional study was conducted in China from July 1 to July 3, 2022, and electronic questionnaires were sent online to MSM individuals of specific institutions. Men, aged 18 or olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 32 publications
(37 reference statements)
4
38
3
Order By: Relevance
“…In the present study, of concern was the knowledge gap about the groups at risk which ranged from 4% for those who indicated HCWs/laboratory personnel to 12.8% for elderly, frail, and people with underlying immune deficiencies. A considerably higher value has been observed in the previously cited survey among men who have sex with men with 40.2% of the respondents that correctly indicated them as high-risk group (35). The lack of knowledge of the disease, how it is transmitted as well as regarding risk groups is troubling because knowing is a prerequisite to facilitate the HCWs for an effective implementation of a successful control and educational activities and, therefore, this may have negative effects upon control and prevention efforts.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In the present study, of concern was the knowledge gap about the groups at risk which ranged from 4% for those who indicated HCWs/laboratory personnel to 12.8% for elderly, frail, and people with underlying immune deficiencies. A considerably higher value has been observed in the previously cited survey among men who have sex with men with 40.2% of the respondents that correctly indicated them as high-risk group (35). The lack of knowledge of the disease, how it is transmitted as well as regarding risk groups is troubling because knowing is a prerequisite to facilitate the HCWs for an effective implementation of a successful control and educational activities and, therefore, this may have negative effects upon control and prevention efforts.…”
Section: Discussionmentioning
confidence: 63%
“…The present finding does not allow inferring the basis on which this belief emerged, but we may speculate that it might have arisen from the fact that only a small number of respondents correctly indicated themselves as a group at risk. A previous study showed that 49.6% of HCWs in Saudi Arabia was afraid of contracting mpox (28) and in the already mentioned survey in Turkey 20.1% of participants were more concerned about mpox than COVID-19 (33), whereas 75% of men who have sex with men showed concerns about their susceptibility to mpox infection (35).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 During the current monkeypox epidemic, as of September 20, 2022, six crosssectional studies have investigated the awareness about monkeypox, among which five focused on the public, medical professionals or students (in Italian, Saudi Arabia, Jordan, the United Arab Emirates, and the United States), [20][21][22][23][24] and one focused on MSM in China. 25 Moreover, studies on monkeypox vaccination hesitancy toward MSM in China were severely absent. Therefore, our study aims to assess the level and correlates of monkeypox vaccination hesitancy among MSM in China.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the perception and acceptance of the vaccination against mpox in this high-risk group around the world. There is one study in the Netherlands in 2022 that reveals that 81.5% of gays, bisexuals, and MSM agreed with receiving the mpox vaccine [20] while another study made in China in the MSM population reports that 90,2% also agreed [21]. However, there are no studies in Latin America focusing on the acceptance of mpox vaccination in the MSM population, despite the high incidence reported in the Americas, making 87.8% of the cases worldwide by February 2023.…”
Section: Introductionmentioning
confidence: 99%